2011
DOI: 10.1177/0194599811423638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and Estrogen Replacement Therapy on Laryngeal Tissue

Abstract: On the basis of histopathological evaluations, it was shown that estrogen replacement helped to improve laryngeal changes due to experimentally induced menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This observation is also consistent with the loss of cilia induced by estrogen deficiency in the laryngeal mucosa of rats [41]. We found that the amount of MC cells is also increased by T and EE2 (Figure 5A-D), It has been shown that a T enhances ciliogenesis and MC cell amounts in female gerbils prostate mucosa [20], and that a natural increase of T and E2 is linked to more MC cells in oviduct epithelia of tetrapods [16].…”
Section: Discussionsupporting
confidence: 88%
“…This observation is also consistent with the loss of cilia induced by estrogen deficiency in the laryngeal mucosa of rats [41]. We found that the amount of MC cells is also increased by T and EE2 (Figure 5A-D), It has been shown that a T enhances ciliogenesis and MC cell amounts in female gerbils prostate mucosa [20], and that a natural increase of T and E2 is linked to more MC cells in oviduct epithelia of tetrapods [16].…”
Section: Discussionsupporting
confidence: 88%
“…In female rats, sex hormones are critical to homeostasis of the pre-menopausal vocal fold mucosal tissues [64][65][66]. Several studies have demonstrated that removal of the ovaries (elimination of ovarian hormones) results in the remodeling of the vocal fold mucosa including the following: decreased cellular layers of the epithelium, increased edema of the lamina propria, and decreased collagen I, hyaluronic acid, and elastin of the lamina propria [64][65][66]. Although ovariectomy procedures have demonstrated vocal fold mucosal remodeling, orchiectomy procedures in male rats have not resulted in significant remodeling [64].…”
Section: Sex Differences In Vocal Fold Mucosamentioning
confidence: 99%
“…Loss of estrogen through surgically induced menopause in female rats increased vocal fold inflammation, edema, and vasodilation, and eliminated vocalizations during mating. 11,12 However, the effects of estrogen on the muscular portion of the vocal fold is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the rat model suggests that sex hormones affect the outer vibratory layer and, consequently, vocal fold function. Loss of estrogen through surgically induced menopause in female rats increased vocal fold inflammation, edema, and vasodilation, and eliminated vocalizations during mating 11,12 . However, the effects of estrogen on the muscular portion of the vocal fold is unknown.…”
Section: Introductionmentioning
confidence: 99%